Penerapan Hidup Sehat dengan Mengkonsumsi Madu dan Vitamin untuk Meningkatkan Imunitas Petugas Kesehatan serta Mencegah Covid-19 Di RSUD Kardinah Kota Tegal - Rahmanindar, Nora; Zulfiana, Evi; Harnawati, Riska Arsita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The Covid-19 virus has become a global pandemic that has claimed many lives. The Covid-19 virus is worrying because it is transmitted very quickly and everyone is at risk of contracting it. In Indonesia, Covid-19 has seen more than 141,000 positive cases. The Corona or Covid-19 virus which is increasingly prevalent in a number of countries, now everyone is required to start increasing stamina, including health workers because health workers are at the forefront of handling positive patients with corona virus or Covid-19 infections. What is very important is that health workers must be healthy to ensure that they can be fulfilled so that the immune system remains stable and healthy to deal with corona patients who are currently in a pandemic, so that dangerous viruses do not easily attack. The risk of contracting the Covid 19 disease for health workers is very large, even many cases where health workers have died in handling cases of Covid-19 disease. The aim of this service is to improve the quality of health workers specifically to handle Covid-19, increase immunity by consuming vitamin C and honey during the Covid-19 Pandemic at RSUD Kardinah, Tegal City. Service method by providing honey and vitamins to health workers who handle Covid-19 at the Kardinah Hospital, Tegal City. Community service activities in the form of giving honey, vitamin C and isotonic drinks for the immune system of health workers handling Covid-19 patients at Kardinah Hospital in Tegal City were received by the Director of Kardinah Hospital, Tegal City, namely Dr. Heri Susanto, Sp.A. This activity was held on 18-19 May 2020.